Guidelines for contributors (2008)
Our Purpose The PROFILE Journal is mainly interested in sharing the results of classroom research projects undertaken by primary and secondary school teachers as well as adult teachers while taking part in the Professional Development Programmes carried out by the Foreign Languages Department at the Universidad Nacional de Colombia. It also includes articles written by teacher educators and guest teachers willing to disseminate innovations and research findings.